The Relationship Between Knowledge And Covid-19 Preventive Behaviors Among Pregnant Women At PMB Lasmitasari, S.ST - Misna Tazkiah; Isti Qomah (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2023)
COVID-19 is a disease caused by the coronavirus. The COVID-19 pandemic poses a threat to all individuals, including pregnant women. It is essential for pregnant women to possess comprehensive knowledge about COVID-19 and to implement preventive measures to mitigate the risk of exposure to this disease. This study aims to analyze the relationship between knowledge about COVID-19 and COVID-19 preventive behaviors among pregnant women at PMB Lasmitasari, S.ST in 2020. The study population comprised all pregnant women who underwent pregnancy check-ups (antenatal visits) at PMB Lasmitasari, S.ST in July 2020, totaling 172 people. The sample comprised of 60 pregnant women who underwent pregnancy check-ups at PMB Lasmitasari, S.ST during the same period. The sampling technique employed was accidental sampling, and data collection was conducted via a questionnaire. The findings revealed that the majority of pregnant women exhibited a poor knowledge about COVID-19, with less than 25 people (41.7%) exhibiting adequate knowledge. Furthermore, the highest proportion of pregnant women engaging in COVID-19 preventive behaviors numbered less than 33 people (55.0%). Importantly, a significant relationship was observed between knowledge about COVID-19 and COVID-19 preventive behaviors among pregnant women at PMB Lasmitasari, S.ST (p = 0.000). Consequently, it is recommended that healthcare professionals intensify health promotion initiatives concerning COVID-19 within the broader community, with a specific focus on pregnant women, leveraging electronic media, mass communication channels, and social media platforms.